Crave, Like, Eat: Determinants of Food Intake in a Sample of Children and Adolescents with a Wide Range in Body Mass - Hofmann, Johannes; Meule, Adrian; Reichenberger, Julia; Weghuber, Daniel; Ardelt-Gattinger, Elisabeth; Blechert, Jens (Frontiers in Psychology, 2016)
Obesity is heterogeneous condition with obese individuals displaying different eating patterns. Growing evidence suggests that there is a subgroup of obese adults that is marked by frequent and intense food cravings and addiction-like consumption of high-calorie foods. Little is known, however, about such a subgroup of obese individuals in childhood and adolescence. In the present study, a sample of children and adolescents with a wide range in body mass was investigated and trait food craving, liking for and intake of high- and low-calorie foods was measured. One-hundred and forty-two children and adolescents (51.4% female, n = 73; Mage = 13.7 years, SD = 2.25; MBMI-SDS = 1.26, SD = 1.50) completed the Food Cravings Questionnaire - Trait, then viewed pictures of high- and low-calorie foods and rated their liking for them, and subsequently consumed some of these foods in a bogus taste test. Contrary to expectations, higher body mass was associated with lower consumption of high-calorie foods. However, there was an interaction between body mass and trait food craving when predicting food consumption: in obese participants, higher trait food craving was associated with higher consumption of high-calorie foods and this association was not found in normal-weight participants. The relationship between trait food craving and high-calorie food consumption within obese individuals was mediated by higher liking for high-calorie foods (but not by liking for low-calorie foods). Thus, similar to adults, a subgroup of obese children and adolescents - characterized by high trait food craving - seems to exist, calling for specific targeted treatment strategies.